Capitanejo Under Fire: Memories of a Guerrilla Takeover - Toloza Núñez, Germán Guillermo; Figueroa Salamanca , Helwar Hernando (Universidad Pedagógica y Tecnológica de Colombia, 2024)
The text narrates the events that occurred on the night ofAugust 30, 1996, when the Revolutionary Armed Forcesof Colombia-People's Army (FARC-EP) took control of theMunicipality of Capitanejo-Santander. It explores howthe residents remember this event and the significance itholds for the people of Capitanejo, a narrative laden withviolence from the past. The study is based on semi-structured interviews, contrasted with press archives from the time, police records, and research on the armed conflict in the region. The information is analyzed in light of the theoretical contributions of Pierre Nora, Roger Chartier, and Danièle Hervieu-Léger. The article highlights how the residents of Capitanejo remember that night, described as the beginning of a new cycle of violence, as paramilitary forces arrived after the guerrilla's establishment, reinforcing a violent past that, at times, seems to collectively define them. The memories of that tragic night and the narratives of the people of Capitanejo demonstrate how memories and representations have contributed to the construction of a common identity around violence, leading to a lack of recognition of their diverse past and efforts to seek a dignified and peaceful life.